A Guide For Authors, Translators, and Copy-Editors IIIT Style Sheet - London, IIIT (International Institute of Islamic Thought, 2002)
This is a concise guide for authors, translators, revisers, copy-editors, and proof-readers involved in the production of manuscripts for publications. A brief overview of successive stages in the production process is given along with guidelines on how to prepare and submit work. The Guide also contains pointers on grammar, and American-English punctuation and spelling; instructions on citing references and bibliographical information; guidelines on transliterating Arabic terms and phrases; and tips on capitalization, especially in relation to Arabic terminology. The Guide as a whole is the outcome of consultations among people with many years of experience in preparing works for publication. In addition to offering sound advice on dealing with some of the common difficulties and problems encountered in translating material from Arabic to English, it also highlights a strategy for translation and defines the task of the author, translator and copy-editor. The Guide is also useful for those who want to standardize format across their publications and ensure consistency in their work, particularly when working with material translated from Arabic. The Guide as a whole is the outcome of consultations among people with many years of experience in preparing works for publication. In addition to offering sound advice on dealing with some of the common difficulties and problems encountered in translating material from Arabic to English, it also highlights a strategy for translation and defines the task of the author, translator and copyeditor. The Guide is also useful for those who want to standardize format across their publications and ensure consistency in their work, particularly when working with material translated from Arabic.